(untitled) (Revista Electrónica Calidad en la Educación Superior, 2019)
The main purpose of the essay is to present diverse technological competencies that teachers require in this new digital century with the intention of considering them when planning workshops for public universities in Costa Rica. In this way, the importance of this article relies on understanding that the implementation of Information and Communication Technologies (ICT) in education isolated does not guarantee a better quality. For this reason, the current challenge in the Costa Rican education consists on improving the educational learning process with the implementation of ICT. Currently, Costa Rica is investing lots of effort on handling this challenge, and it has been successful. Nevertheless, it is possible to conclude that the investigation and training process needs to be enhanced. Also, it is possible to conclude that the virtualization of Costa Rican higher education is just starting.